2021
DOI: 10.1021/acs.estlett.1c00222
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Distribution of Legacy and Novel Per- and Polyfluoroalkyl Substances in Juvenile Seabirds

Abstract: Of the thousands of per- and polyfluoroalkyl substances (PFAS) in the environment, few have been investigated in detail. In this study, we analyzed 36 legacy and emerging PFAS in multiple seabird tissues collected from individuals from Massachusetts Bay, Narragansett Bay, and the Cape Fear River Estuary. PFOS was the dominant compound across multiple tissues, while long-chain perfluorinated carboxylic acids (PFCAs) dominated in brain (mean = 44% of total concentrations). Emerging perfluoroalkyl ether acids (PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 40 publications
7
27
0
Order By: Relevance
“…As anticipated from previous wildlife exposure studies along the Cape Fear River, PFOS was the dominant PFAS detected in alligator serum (Guillette et al 2020; Robuck et al 2021) We detected PFOS in 100% of samples analyzed and it accounted for 79.7% and 75.8% of the total PFAS present in alligator serum samples from the CFR and LW respectively. The median number of PFAS congeners detected in serum samples from CFR alligators was 10 (range 4-12), whereas a median of 5 (range 2-9) were detected in LW samples (Table S3).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As anticipated from previous wildlife exposure studies along the Cape Fear River, PFOS was the dominant PFAS detected in alligator serum (Guillette et al 2020; Robuck et al 2021) We detected PFOS in 100% of samples analyzed and it accounted for 79.7% and 75.8% of the total PFAS present in alligator serum samples from the CFR and LW respectively. The median number of PFAS congeners detected in serum samples from CFR alligators was 10 (range 4-12), whereas a median of 5 (range 2-9) were detected in LW samples (Table S3).…”
Section: Resultssupporting
confidence: 81%
“…Recently, total organic fluorine analysis detected extremely high sum PFAS concentrations in excess of 100,000 ng/L in the Cape Fear River at drinking water treatment plant intakes suggesting that humans and aquatic ecosystems in the Cape Fear River basin have been experiencing very high levels of total PFAS exposure (Zhang et al, 2019). The potential for impacts on both ecosystems and human populations from this contamination has been confirmed by wildlife and human population based PFAS exposure studies that found increased levels of PFAS in fish, birds, and humans living near the Cape Fear River (Guillette et al 2020;Kotlarz et al 2020;Robuck et al 2021). The public and environmental health impacts of longterm exposures resulting from undocumented PFAS discharge are largely unknown.…”
Section: Highlightsmentioning
confidence: 99%
“…As the brain is most susceptible to penetration by lipophilic compounds, there is cause for concern that some PFAS may elicit considerable neurotoxic effects. In addition, the blood is one of the major compartments in which PFAS partitions, due to the relatively low affinity binding of PFAS to serum albumin ( Maestri et al, 2006 ; Kudo et al, 2007 ; Bogdanska et al, 2011 ; Jackson et al, 2021 ; Robuck et al, 2021 ). Thus, due to the highly vascularized nature of the brain, there is enhanced risk of brain exposure to toxicants found in the blood, including PFAS.…”
Section: Introductionmentioning
confidence: 99%
“…PFAS are known environmental pollutants which contaminate ground and surface water worldwide [4–7] . Many PFAS are persistent in the environment and bioaccumulative, having been detected in human and other animal tissue across the globe, [8–11] and exposure to some PFAS leads to adverse health and environmental outcomes [12–15] …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] PFAS are known environmental pollutants which contaminate ground and surface water worldwide. [4][5][6][7] Many PFAS are persistent in the environment and bioaccumulative, having been detected in human and other animal tissue across the globe, [8][9][10][11] and exposure to some PFAS leads to adverse health and environmental outcomes. [12][13][14][15] The potential health effects of PFAS exposure, along with the expected regulation of these pollutants, has led to increased interest in PFAS remediation technologies.…”
Section: Introductionmentioning
confidence: 99%